Effects of the planetary migration on some primordial satellites of the outer planets - Deienno, R. [UNESP]; Yokoyama, T. [UNESP]; Nogueira, E. C.; Callegari, N. [UNESP]; Santos, M. T. (Edp Sciences S A, 2011)
Context. During the first hundred million years after the formation of our solar system, the four giant planets are believed to have migrated significantly (by up approximate to 20 AU). The current scenario and dynamics of the satellites of these planets must be the result of both the initial conditions of their formation and this early extensive migrational episode.Aims. We examine the effects of the migration on the primordial satellites of Uranus.Methods. We use the Nice model to generate templates for the evolution of the four giant planets and record the time history of these planets and important close encounters. The satellites are then added to Uranus and these objects are integrated according to the dynamics stored in the templates.Results. We show that Oberon is the outermost regular satellite of Uranus that is able to resist the close encounters during the extensive migrational episode. Some theories predict that Uranus' satellites can form out to a 57 R-U distance from the planet, but we show that even those at approximate to 27 R-U from the planet cannot support the instabilities that appeared during migration. Close objects, such as the current regular satellites of Uranus, can survive quite stably and we are able to place some constraints on the masses of the planetesimals that have close encounters. For instance, if an object with mass >= 10(-9) M-circle dot approaches at distances less than or similar to 23 R-U from Uranus, the regular satellites can be destabilized or their eccentricities or inclinations excited to some non-compatibles values. We also find that planet-planetesimal close encounters can generate capture. In this way, we present a promising means of explaining the origin of the irregular satellites of Uranus. The importance of the oblateness of the planet, and the Sun for just-captured planetesimals is also shown.
Keywords: celestial mechanics; planets and satellites: general; planets and satellites: individual: Uranus